SELF-DIRECTED LEARNING PRACTICE IN CRITICAL SPEAKING CLASS: CHALLENGES AND SOLUTIONS IN THE HIGHER EDUCATION EFL CONTEXT - Handayani, Ika; Suseno, Muchlas; -, Romdani (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
In the context of higher education, this qualitative study investigates the implementation of self-directed learning (SDL) in critical speaking class for English as Foreign Language. As the need for critical thinking and fluent English in global communication grows, it is crucial that students be able to take charge of their own learning in speaking classes. The study looks into the coping mechanism, challenges and experiences of EFL university students who participate in SDL for critical speaking assignments. Semi-structured interview and classroom observation were used to gather data. Thematic analysis revealed several challenges including low self confidence, limited linguistic resources, lack of exposure to authentic materials and inadequate instructor scaffolding. Students overcome these challenges by implementing a variety of strategies, including reflective practices, peer collaboration and the use of digital platforms. The results emphasize the need for more supportive learning environment that balances autonomy with guided instruction. This study provides more pedagogical insights for educators who want to improve learner independence in EFL contexts and promote effective SDL in critical speaking instruction.